FINANCIAL CONTROL AND THE MANAGEMENT OF LOCAL GOVERNMENT FUNDS: IMPLICATIONS FOR THE DELIVERY OF SOCIAL INFRASTRUCTURE - Aja, Innocent Ngene (African Journal of Social and Behavioural Sciences, 2026)
This paper investigates the mechanisms of financial control within local governments in Nigeria and considers their implications for the delivery of social infrastructure. Local governments are central to providing essential services such as healthcare, education, and transportation, yet they face persistent challenges in financial management, including corruption, embezzlement, and weak oversight systems. Guided by the Principal-Agent Theory, the study examines the dynamics between local government officials (agents) and the public (principals), showing how conflicts of interest contribute to poor financial control and inefficient resource allocation. Methodologically, the paper adopts a qualitative, conceptual approach, relying on secondary sources such as audit reports, government publications, and existing scholarly literature. Rather than presenting systematic empirical findings, the analysis synthesizes documented cases and comparative experiences to highlight how financial mismanagement undermines infrastructure delivery, erodes public trust, and widens service gaps. The study also reviews examples of financial management practices from other jurisdictions to generate informed recommendations. Principal strategies identified include adopting digital platforms for expenditure tracking, promoting citizen participation in budgeting, and enhancing independent oversight mechanisms. These strategies are offered as informed proposals rather than empirically validated outcomes, reflecting the study’s conceptual orientation. By situating the analysis within the Principal-Agent framework and drawing on verifiable audit evidence, the paper contributes to a deeper understanding of financial governance at the local level in Nigeria and identifies potential pathways for reform to improve transparency, accountability, and infrastructure delivery.